Soccer - The disrupted game: Perturbations as a cause for scoring success - Dreier, S.; Maier, J.; Brunnschneider, M.; Keiner, M. (International Journal of Sports Science & Coaching, 2024)
This study was designed to analyze goal-scoring in elite soccer, drawing on an extensive dataset encompassing 892 goals and 3496 perturbations recorded in the German 2nd Bundesliga. A qualitative approach was used to analyze perturbations, which are technical-tactical situations that disrupt opponent stability and facilitate goal success. The research differentiated between offensive and defensive perturbations, characteristics of initiating disruptive perturbations, their zones of occurrence, directions of play, significant playing positions, and their contributions toward goals, as well as perturbation chains leading to goal success. The analysis determined that an average of 3.9 perturbations is typically required to forge a goal-scoring opportunity against the opposition. It was revealed that 39% of initiating perturbations were defensive, predominantly characterized by misplaced passes. In contrast, 43% were attributed to offensive group tactical perturbations, such as low passes, long-distance kicks, and crosses. Only 18% stemmed from individual perturbations, with runs without the ball and dribbling to bypass the opponent being the primary occurrences. An analysis focusing solely on the immediate actions can lead to misinterpretations regarding the genesis of goals. While only 79 goals resulted from a single perturbation, most commonly a shot on goal, 813 goals emerged from scenarios involving two or more perturbations.